Pretreatments applied to microalgae residues to enhance anaerobic digestion - Rodrigues, M.P. (2019)
Biomass of microalga Chlorella protothecoides, grown under autotrophic and heterotrophic conditions and subjected to pretreatments, were energetically valorized through anaerobic digestion process according to the substrates: autotrophic algae (A), heterotrophic algae (H), heterotrophic algae extracted (HE), autoclave pretreated heterotrophic algae (HPA), enzyme pretreated heterotrophic algae (HPE), ultrasound pretreated heterotrophic algae (HPU), and inoculum (I). Despite the application of pretreatments, the highest methane production was obtained in the algae extracted digestion with 172 mL CH4, against 153, 126 and 142 mL obtained in HPA, HPE and HPU, respectively. The COD removal capacity was higher in the HPA sample while the TS and VS removal reached higher values in the autotrophic alga.